Pelatihan Petanque Pada Guru-Guru Olahraga di jawa Timur - Ristanto, Kolektus Oky (Journal of Sport Moovera (JSM), 2023)
Sport has many benefits for the body both physically and spiritually. This impact can increase the life expectancy of the Indonesian people. When doing sports, the human body will carry out a natural detoxification process so that toxins in the body, bad fats, cholesterol, uric acid, blood sugar and others will affect the body. When the body is fresh and physically strong, the level of productivity produced is also higher. Indonesian people are superior in various fields. The many choices of sports branches allow people to choose varied and make it fun. The form of the sport is Petanque, this sport is related to throwing boules (balls) where a player must be in a circle to throw the ball that has been provided. Petanque games are easy for all ages, both children and the elderly. The ease of this game will encourage the motivation of the Indonesian people to exercise actively and regularly. Petanque sport only entered Indonesia around the 2000s. This sport is different from other sports because it demands body movement and accuracy in throwing. This game technique is very simple but relies on extraordinary balance for precision and on target when throwing. It is very necessary to introduce petanque games at the provincial level of East Java, especially to the school environment, this sport will quickly develop and be easily recognized by the community and sports teachers at both elementary, middle and high school levels if the introduction is done properly. This socialization will be targeted to PJOK teachers at MGMP in the East Java Region.